Mineral nutrition and fertilization of sweet potato - Fernandes, Adalton Mazetti [UNESP]; Ribeiro, Nathalia Pereira [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
Sweet potato (Ipomoea batatas L.) is a versatile crop, but it is often grown in marginal and low-fertility areas, which reflects storage root yields far below its potential. For this reason, balanced liming and fertilization in sweet potato are essential to increase crop yield. Based on this approach, themes related to the nutritional requirements of sweet potato are presented and discussed considering the main cultivars currently used in Brazil as well as references for rational fertilization management in this crop. Sweet potato is a crop that absorbs large amounts of nutrients during its development cycle, but this should not be used as a prerogative to excessively increase the fertilizer rates applied in this root crop. As a strategy for rational fertilization management, one should take advantage of the ability of this crop to associate with N-fixing microorganisms, thus reducing the use of mineral N. Moreover, it is necessary to encourage the use of organic fertilizer, whether using animal manure or green manure. In addition to increasing storage root yield and improving storage root shape, organic fertilizers can partially replace mineral chemical fertilizers. Studies aimed at updating cultivar-specific potassium and phosphate fertilizer recommendations should also be encouraged, as well as research addressing micronutrient supply for sweet potato.
Nutrição mineral e adubação da batata-doce
Keywords: Ipomoea batatas L.; Mineral fertilizer; Nutrients; Nutritional status; Organic fertilizer